(untitled) (Research, Society and Development, 2022)
Studies related to the innovation process in public management have become recurrent in the organizational field. Thus, in order to contribute to the dissemination of this theme, the present study aims to understand the process of innovation in Brazilian public management, making it possible to identify its potential and implications. The investigation is configured as a theoretical study, having a qualitative approach as a methodological procedure, thus, a bibliographic survey was carried out in the main bases of Brazilian and international academic research. In the treatment of the obtained data, the method of interpretive analysis was used, with emphasis on the understanding of the identified examples and on the interpretation of the meanings. In the discussion of the results, it was observed that innovation in Brazilian public management is still in the consolidation phase, given that there is still a long way to go, so that its main potential comes from the use of technologies. and its implications collide with the bureaucratic processes of formalization and the resistance of the servers and/or collaborators. In addition, it is observed that Information and Communication Technologies (ICTs) have made possible a new model in Brazilian public management, among the numerous increments of innovation, the Transparency Portal and the Electronic Government (e-gov) stand out. Furthermore, it is clear that innovation positively impacts services in the Brazilian public sector.